1999
DOI: 10.1029/1999jd900418
|View full text |Cite
|
Sign up to set email alerts
|

A study of enhanced fair‐weather electric fields occurring soon after sunrise

Abstract: Abstract. In this paper we describe several series of electric field soundings made in the lowest few hundred meters above the ground on 6 days at Kennedy Space Center in Florida. These soundings are used to determine the charge density and thickness of the charged electrode layer just above the surface of the Earth both before and after sunrise during fair weather. On most of the days considered, there was an anomalous enhancement in the ground-level electric field that was probably associated with the "sunri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 18 publications
0
26
0
5
Order By: Relevance
“…Franke (1949) mathematically proved that the diurnal variation of the E would generally be a curve with double oscillations following vertical atmospheric mass exchange over land. Muhleisen (1956) has experimentally dealt with the effect of presence of water in different forms and condensation nuclei on atmospheric potential to a great extent. The 'Sunrise Effect' observations of E by Law (1963) showed that space charge and E appears to be more closely related to each other than to any other variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Franke (1949) mathematically proved that the diurnal variation of the E would generally be a curve with double oscillations following vertical atmospheric mass exchange over land. Muhleisen (1956) has experimentally dealt with the effect of presence of water in different forms and condensation nuclei on atmospheric potential to a great extent. The 'Sunrise Effect' observations of E by Law (1963) showed that space charge and E appears to be more closely related to each other than to any other variable.…”
Section: Introductionmentioning
confidence: 99%
“…The 'Sunrise Effect' observations of E by Law (1963) showed that space charge and E appears to be more closely related to each other than to any other variable. Marshall et al (1999) studied the 'Enhanced Sunrise Effect' to show that it does not contain to the layers close to ground and nearness to water bodies significantly elevates the values reached. Of recent a school of thought (Delgado et al, 2003) is evolving that it is not the E that is controlled by pollution dependent conductivity but the pollutants rearrange themselves as per the prevalent E depending on their dipole moment.…”
Section: Introductionmentioning
confidence: 99%
“…The sunrise effect was extensively described by Marshall et al (1999), who focused particularly on PG response to positive space charge transpositions. Other authors (Law 1963;Chalmers 1967;Kamra 1982) also mentioned the sunrise effect, among which Kamra (1982) and Law (1963) observed a sign reversal of space charge from negative to positive at the moment of sunrise, coinciding with PG increase.…”
Section: Diurnal and Seasonal Pg Variationmentioning
confidence: 99%
“…Other authors (Law 1963;Chalmers 1967;Kamra 1982) also mentioned the sunrise effect, among which Kamra (1982) and Law (1963) observed a sign reversal of space charge from negative to positive at the moment of sunrise, coinciding with PG increase. According to Marshall et al (1999), the start of the morning convection caused by solar heating leads to the destruction of a shallow positively charged layer (electrode layer) that was built up during the night and overlies the very first decimeters of the ground (Crozier 1963). The dilution of the electrode layer just after sunrise owing to increasing turbulence transports gradually more and more positive charges over the EFM enhancing eventually PG (Marshall et al 1999).…”
Section: Diurnal and Seasonal Pg Variationmentioning
confidence: 99%
See 1 more Smart Citation